Drawing the Map: Siting Architecture - Anne Bordeleau; Liana Bresler (Footprint)
Architects increasingly favour mapping as a means of documentation. Through maps, they question and define the boundaries of their architectural intervention, the premise being that if they can adequately delaminate and map the site's found conditions, they may achieve a more complex understanding of the said site.